(untitled) (Journal of Hama University, 2022)
Thirty five birds eight day old were vaccinated against Newcastle disease virus with live attenuated vaccine (cloned strain) through drinking water, the birds were housed in field conditions. Histologic samples were collected for studying histopathologic changes in small intestine after 2, 24, 48, 96 and 144 of vaccine administration. Samples were fixed in buffered formalin solution 10% and embedded in Paraffin. Histologic sections 4 microns were made and stained with Hematoxline-Eosin and Giemsa stain. Macroscopic exam revealed a few hemorrhagic points and light congestion after 48 hour of vaccine administration which continued until the end of experiment. Microscopic exam revealed increase in mast cells number after 2 hour of vaccination. Focal infiltrations of Heterophils and Mast cells were observed in mucosal Lamina Propria accompanied with congestion in blood vessels, light Edema and Goblet cells hypertrophy after 24 hour of vaccination. Microvilli were removed focally in small intestine beside sever infiltration of Heterophils after 48 hour of vaccination. Focal necrosis occurred in epithelial cells and goblet cells later. Lymphocytes and macrophages appeared obviously after 96 hour of vaccination and became predominantly after 144 hour. Hyperplasia in intestinal crypt were observed at the end of experiment. Conclusion: Focal necrosis occurred in epithelial cells and goblet cells of small intestine. These changes associated with Innate immune response after vaccination with live attenuated cloned strain of NDV consist of mast cells, heterophilis and macrophages which composed of lymphocytes, macrophages and plasma cells later.